Effective Use of PV Systems for a Sustainable Energy Solution: A Case Study - Kaya, Fikret; Akpolat, Alper Nabi; Akar, Onur (Fırat University, 2025)
Energy demand is rapidly increasing alongside global population growth. Instead of relying on fossil fuels, which harm the environment, technological advances have enabled the use of renewable energy sources. Solar energy is increasingly recognized as a vital resource among many renewable options, and its usage is expected to grow even more in the future. Photovoltaic (PV) solar panels enable detached houses, especially in remote settlements, to meet their electricity needs. The most important component that converts the energy produced in this PV system to the desired level is the DC-DC converter. One of the most effective methods to obtain the highest amount of power from the PV panel is the application of the Maximum Power Point Tracking (MPPT) technique to the DC-DC converter. Additionally, battery systems have proven to be a viable solution for meeting energy demand during periods when PV panels do not produce electricity. In this study, an efficient working structure has been developed using the MPPT algorithm to meet the load's needs while storing a portion of the electrical energy obtained from five parallel-connected PV panels in a lithium-ion battery. Ensures an uninterrupted energy flow at the highest power output using the most appropriate technique. MATLAB/Simulink software was employed for system design and simulation. Solar radiation data from the summer period of the Enez district in Edirne province were selected for analysis. A lithium-ion battery type was utilized in the system. The results show that energy from the PV panel is insufficient during the early hours of sunrise, at which point energy demand is met by the battery. After a certain hour, the PV panel satisfies the required energy demand, and any excess energy is stored in the battery. This system demonstrates an efficient energy management structure that ensures continuous power supply for off-grid households.

Dünyada nüfus artışı ile birlikte enerji talebi de hızla artış göstermektedir. Çevre üzerinde bozucu etkiler oluşturmuş olan fosil yakıtlar yerine teknoloji alanındaki ilerlemeler sayesinde yenilenebilir enerji kaynaklarının kullanılmasının önünü açılmıştır. Güneş enerjisi, birçok yenilenebilir kaynak arasında gittikçe önemi anlaşılan ve gelecekte de kullanımı daha da artacak olan bir kaynak türüdür. Fotovoltaik (FV) güneş panelleri özellikle uzak yerleşim yerlerinde müstakil evlerin elektrik yüklerinin ihtiyaç duyduğu elektrik ihtiyacını karşılamalarına olanak sağlamaktadır. Bu FV sisteminde üretilen enerjinin istenilen seviyedeki enerji miktarına dönüşümünü sağlayan en önemli bileşen DA-DA dönüştürücüdür. FV panelinden en yüksek miktarda gücü alabilmek için en uygun yöntemlerden biri de DA-DA dönüştürücüye Maksimum Güç Noktası İzleme (MPPT) tekniği uygulamasıdır. FV panellerin üretim yapmadığı zaman dilimlerinde enerji ihtiyacının karşılanması için batarya sistemleri kullanmak bir çözüm olmuştur. Bu çalışmada, MPPT algoritması yardımıyla ile beş adet paralel bağlı FV panelden azami şekilde elde edilen elektrik enerjisinin bir kısmı yükün ihtiyacını karşılarken diğer kısmı ise Li-Ion tipi bataryada depolanması amaçlanarak verimli bir çalışma yapısı oluşturulmuştur. Böylece kesintisiz bir enerji akışı sağlanması düşünülmüştür. Sistem tasarımı ve simülasyonu için MATLAB/Simulink yazılımı kullanılmıştır. Güneş ışınım verileri olarak Edirne ili Enez ilçesinin yaz dönemine ait veriler seçilmiştir. Batarya tipi olarak Lityum-İyon tip kullanılmıştır. Sonuçlara baktığımızda, gün doğumunun ilk saatlerinde FV panelden gelen enerjinin yetersiz olduğu ve bu noktada enerjinin bataryadan karşılandığı belirli bir saatten sonra ise panelin ihtiyaç duyulan enerjiyi karşıladığı ve fazla üretilen enerjinin bataryada depolandığı görülmektedir. Bu sayede enerji yönetim sistemiyle kesintisiz enerji akışı en yüksek güçte ve en uygun teknikle sağlanmış olmaktadır.
Sürdürülebilir Enerji Çözümü için FV Sistemlerinin Etkin Kullanımı: Bir Vaka Çalışması
Keywords: Photovoltaic Power Systems; Fotovoltaik Güç Sistemleri